Assessing the costs and environmental benefits of IMO regulations of ship-originated SOx and NOx emissions in the Baltic Sea - Repka Sari; Erkkilä-Välimäki Anne; Jonson Jan Eiof; Posch Maximilian; Törrönen Janne; Jalkanen Jukka Pekka (Springer, 2022)
To assess the value of the environmental benefits of the Sulphur Emission regulation (SECA) that came into force in 2015, changes in depositions of SOx and NOx from ship exhaust gas emissions were modelled and monetized for the Baltic Sea region for the years 2014 and 2016. During this period, the total deposition of SOx in the study area decreased by 7.3%. The decrease in ship-originated SOx deposition from 38 kt to 3.4 kt (by over 88%) was translated into a monetary value for the ecosystem impacts of nearly 130 million USD, according to the EcoValue08 model. This is less than the modelled health benefits, but it is not insignificant. For NOx, there was no decreasing trend. The exceedance of the critical loads of SOx and NOx was also estimated. The effect of Baltic shipping on the exceedance of critical loads of acidification after SECA is very small, but Baltic shipping still has a considerable effect on the exceedance of critical loads for eutrophication.